Navigating Technology-Supported English Learning in Vocational Higher Education: Insights from the First-Year Indonesian Polytechnic Students - Beni Wijaya; Sri Endah Kusmartini; Darmaliana Darmaliana; Eli Yeny (Journal of English Language and Education, 2026)
Despite the growing integration of digital technology into English language instruction in vocational higher education, little research has explicitly looked at how technology-supported learning affects learner autonomy, English proficiency, and learning challenges among Indonesian vocational college students. This study examined how first-year students at Politeknik Negeri Sriwijaya, Indonesia, learned English with the aid of technology based on their patterns of technology use, perceptions, contributions and challenges. Data from 474 students were gathered via an online survey utilizing a descriptive quantitative methodology, and descriptive statistics were used for analysis. The results showed that students regularly employed digital technologies to help them learn English (M=3.79, SD=0.95), with online videos, mobile applications, artificial intelligence (AI) tools, and online resources being widely used. Additionally, students showed positive perceptions of technology-supported English learning (M=3.98, SD=1.01), especially with regard to simple access to educational resources, heightened enthusiasm for learning, and enhanced comprehension of lessons. Additionally, it was believed that technology improved English language proficiency (M=3.92, SD=0.98), particularly speaking, listening, and reading. Additionally, the results demonstrated that technology fosters learner autonomy (M=3.81, SD=0.96) by allowing students to autonomously access resources, participate in self-directed learning, and assume more accountability for their educational journey. Despite these advantages, students reported a number of difficulties (M=3.40, SD=0.98), such as the need for more teacher supervision, inadequate internet access, technological difficulties, and learning distractions. Overall, the study shows that technology significantly improves vocational higher education students' English learning experiences, language growth, and learner autonomy. To optimize the advantages of technology-supported English learning, the results emphasize the significance of efficient technology integration, sufficient infrastructure, and pedagogical support.